Correlation of upper and lower extremities isokinetic strength in elite male judokas - Yilmaz, A. K.; Ermis, E.; Kabadayi, M.; Bostanci, Ö. (Journal of Men`s Health, 2020)
Background and purpose: Muscle strength is one of the most physically important parameters during the competition for judokas. Studies have shown that for judokas, strength in especially the knee and shoulder muscles and the strength balance between right and left sides is very important in terms of both staying in balance and doing specific techniques correctly. Our study aims to find out the correlations between isokinetic lower and upper extremity strength in elite judokas and to examine bilateral and contralateral strength ratios.